2020
DOI: 10.3390/ijms21176436
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profile of Barrett’s Esophagus and Gastroesophageal Reflux Disease in the Development of Translational Physiological and Pharmacological Studies

Abstract: Barrett’s esophagus (BE) is a premalignant condition caused by gastroesophageal reflux disease (GERD), where physiological squamous epithelium is replaced by columnar epithelium. Several in vivo and in vitro BE models were developed with questionable translational relevance when implemented separately. Therefore, we aimed to screen Gene Expression Omnibus 2R (GEO2R) databases to establish whether clinical BE molecular profile was comparable with animal and optimized human esophageal squamous cell lines-based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…This could partially be explained by the fact that lowering pH towards pKa values of unconjugated (pKa 5.2–6.2; e.g., deoxycholic acid) or glycine-conjugated (pKa 3.8–4.8; e.g., sodium glycocholate) may unionize bile salts, which makes them more lipophilic and able to enter the epithelial cells by cell membrane rupture and influence intracellular pathways [ 24 ]. This is also in accordance with our previous study, where we observed that acidified BM is more cytotoxic for esophageal HET-1A and EPC2 cells [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…This could partially be explained by the fact that lowering pH towards pKa values of unconjugated (pKa 5.2–6.2; e.g., deoxycholic acid) or glycine-conjugated (pKa 3.8–4.8; e.g., sodium glycocholate) may unionize bile salts, which makes them more lipophilic and able to enter the epithelial cells by cell membrane rupture and influence intracellular pathways [ 24 ]. This is also in accordance with our previous study, where we observed that acidified BM is more cytotoxic for esophageal HET-1A and EPC2 cells [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, highly expressed KRT15 protein may contribute to esophageal carcinoma progression [ 59 ], whereas overexpression of KRT18 in colorectal cancer exerts an oncogenic role [ 60 ]. Moreover, our previously published data confirmed that these markers reflect clinical alterations within an in vitro model of BE [ 21 ]. The expression of COXs (COX1 and COX2, encoded by PTGS1 and PTGS2 ) was linked to the development of GI tumors and early BE-derived neoplastic transformation [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations